Investigating the susceptibility of treatment-resistant oesophageal tumours to natural killer cell-mediated responses - Maher, Stephen; Reynolds, John; Conroy, Melissa (My University, 2023)
The majority of oesophageal adenocarcinoma (OAC) patients do not respond to multimodal treatment regimens and face dismal survival rates. Natural killer (NK) cells are crucial anti-tumour immune cells, and this study investigated the susceptibility of treatment-resistant OAC cells to these potent tumour killers. Natural killer receptor (NKR) ligand expression by OE33CisP (cisplatin-sensitive) and OE33CisR (cisplatin-resistant) cells was investigated. The immunomodulatory effects of OE33CisP and OE33CisR cells on NK cell phenotype and function were assessed. Finally, the impact of chemotherapy regimens on NKR ligand shedding was examined. Our data revealed significantly less surface expression of activating ligands B7-H6, MICA/B, ULBP-3 and activating/inhibitory ligands PVRL-1 and PVRL-4 by OE33CisR cells, compared to OE33CisP cells. Co-culture with OE33CisR cells reduced the frequencies of NKp30+ and NKp46+ NK cells and increased frequencies of TIGIT+, FasL+ and TRAIL+ NK cells. Frequencies of IFN-γ-producing NK cells increased while frequencies of TIM-3+ NK cells decreased after culture with OE33CisP and OE33CisR cells. Frequencies of circulating NKp30+ NK cells were significantly lower in OAC patients with the poorest treatment response and in patients who received FLOT chemotherapy, while B7-H6 shedding by OAC tumour cells was induced by FLOT. Overall, OE33CisR cells express less activating NKR ligands than OE33CisP cells and have differential effects on NKR expression by NK cells. However, neither cell line significantly dampened NK cell cytokine production, death receptor expression or degranulation. In addition, our data indicate that FLOT chemotherapy may promote B7-H6 shedding and immune evasion with detrimental consequences in OAC patients.
ACCEPTED
Keywords: Immunotherapy; NK cell receptors; NK cells; Oesophageal adenocarcinoma; Treatment-resistance; Cancer; Immunology, Inflammation & Infection; Tumour immunology and immunotherapy